Increasing the Field of View for the Cassegrain telescope at the Kryoneri Astronomical Station - Gazeas, Kosmas D. (Recent Advances in Astronomy and Astrophysics, 2006)
During recent observations it was possible to increase the field of view for the Cassegrain telescope at the Kryoneri Astronomical Station of the National Observatory of Athens. The very small area of sky observable with the existing CCD, is a problem when larger fields need to be observed. A focal reducer was installed on the telescope thus increasing the observed area by a factor of about 4. The advantage is faster photometry and detection of very faint stars (>20 mag). A permanent focal reducer should be mounted on the telescope for the benefit of all observers.
Keywords: 95.45.+i; 95.55.Qf; Observatories and site testing; Photometric polarimetric and spectroscopic instrumentation